The Influence of Lifestyle, Personality Traits, and Platform Quality on Impulse Buying on Tiktok Social Commerce - Jikka Ailsa; Zakky Fahma Auliya (Proceeding of International Management Conference and Progressive Papers, 2024)
This study aims to analyze the influence of lifestyle, personality traits, and platform quality on impulse buying on TikTok social commerce. The method used in this research is a quantitative approach with a causal study design, involving 160 respondents aged 15 to 20 years who live in Solo Raya. Data was collected through distributing questionnaires online using Google Form and analyzed with SmartPLS 3.0 software through the SEM-PLS method. The results showed that lifestyle variables have a positive and insignificant effect on impulse purchases, platform quality variables have a negative and insignificant effect on impulse purchases, while personality traits variables have a positive and significant effect on impulse purchases. These findings provide important insights for online entrepreneurs in understanding consumer behavior and designing more effective marketing strategies on social commerce platforms such as TikTok.